2020
DOI: 10.1021/jacs.0c05025
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Enabled Ortho-Selective Aminopyridylation of Alkenes with N-Aminopyridinium Ylides

Abstract: By utilizing an underexplored reactivity mode of N-aminopyridinium ylides, we developed the visible-light-induced ortho-selective aminopyridylation of alkenes via radical-mediated 1,3-dipolar cycloaddition. The photocatalyzed single-electron oxidation of N-aminopyridinium ylides generates the corresponding radical cations that enable previously inaccessible 1,3-cycloaddition with a broader range of alkene substrates. The resulting cycloaddition adducts rapidly undergo subsequent homolytic cleavage of the N–N b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 89 publications
0
61
0
Order By: Relevance
“…During the preparation of this manuscript, the Hong group reported the photocatalytic aminopyridylation of alkenes via radicalmediated 1,3-dipolar cycloaddition and demonstrated that Naminopyridinium ylides would take the role of a 1,3-dipolar radical cation. 19 Our investigation started from the sulfur-alkenylation of activated alkenes that were irradiated with blue LEDs by investigating the reaction of α-phenacyl dithioacetal 1a with styrene 2a to find the optimal conditions, as shown in Table 1.…”
mentioning
confidence: 99%
“…During the preparation of this manuscript, the Hong group reported the photocatalytic aminopyridylation of alkenes via radicalmediated 1,3-dipolar cycloaddition and demonstrated that Naminopyridinium ylides would take the role of a 1,3-dipolar radical cation. 19 Our investigation started from the sulfur-alkenylation of activated alkenes that were irradiated with blue LEDs by investigating the reaction of α-phenacyl dithioacetal 1a with styrene 2a to find the optimal conditions, as shown in Table 1.…”
mentioning
confidence: 99%
“…Inspired by the property of N-aminopyridinium ylides that they are capable of undergoing thermally induced 1,3-dipolar cycloadditions with alkynes, 46 Hong and co-workers reported C2-regioselective aminopyridylation of N-aminopyridinium ylides with alkenes via radical-mediated 1,3-dipolar cycloaddition, which led to excellent C2-regioselectivity (Scheme 31). 47 The reaction exhibited good substrate scope of alkenes, both activated (38a-38d) and unactivated alkenes (38e, 38g) afforded products in moderate to good yield. Styrenes, previously incompatible in pyridylation, 37 showed good reactivity in this transformation (38a-38b, 38f).…”
Section: C2 Selectivitymentioning
confidence: 92%
“…Wu et al in 2019 depicted (Figure 23) a visible-light-mediated Cu-catalyzed difunctionalization of alkene (37) to give azidation product (38) [27]. Here the azidobenziodoxole acts as an azidating agent in the presence of acetonitrile and [Cu(dap) 2 ]PF 6 complex as the photocatalyst.…”
Section: Cu and Pd-catalyzed C-n Bond Formationsmentioning
confidence: 99%
“…Moon et al in 2020 demonstrated an atom-economical visible-light-mediated synthesis of aminopyridylationproduct (56) in the presence of alkenes (55) and N-aminopyridinium ylides (Figure 33) [37]. This environmentally friendly method applies to a wide range of substrates with good functional group tolerance.…”
Section: Mes-catalyzed C-n Bond Formationmentioning
confidence: 99%